2010
DOI: 10.1111/j.1556-4029.2009.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Chilean Children’s Dental Maturation*

Abstract: In forensic science, determining a person's chronological age has become a challenge for researchers. Determining age using dental calcification is becoming increasingly important. The objective of this study is to estimate the dental age of the children's population in Region VIII, Chile. The sample was randomly taken from children under the care of the Faculty of Dentistry at the Universidad de Concepción in Chile. The study encompasses 159 children between 3 and 14 years of age. The dental age was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In a previous study, we showed that the range between chronological and dental age is similar and that the degree of correlation for each sex is also significant (8). In addition, other researchers have observed that skeletal maturation is associated with teeth calcification stages (11,12).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In a previous study, we showed that the range between chronological and dental age is similar and that the degree of correlation for each sex is also significant (8). In addition, other researchers have observed that skeletal maturation is associated with teeth calcification stages (11,12).…”
Section: Discussionmentioning
confidence: 68%
“…This method was initially based on a group of French Canadian children , but Flores et al. demonstrated that the Demirjian method is applicable to Chilean children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In archeology and forensic odontology, age estimation methods can aid to the age identification of a deceased child. They have also been proven valuable when birth data are lacking or doubted in the management of immigration to help to determine physiologic age (1, 2). Additionally, it is of particular interest to the pedodontist and orthodontist as information aids in diagnosis and treatment planning (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…Se han realizado numerosos estudios en diferentes grupos étnicos, analizán-dose niños europeos, asiáticos y sudamericanos, entre otros. Se ha sugerido que puede haber diferentes patrones de maduración dental entre las distintas poblaciones, no sólo entre grupos poblacionales alrededor de todo el mundo, sino también entre individuos de diferentes ciudades o áreas geográficas dentro del mismo país (Cruz-Landeira et al, 2010;Eid et al, 2002;Lee et al, 2008;Liversidge et al, 1999;Moananui et al, 2008;Nyström et al, 2000;Nyström et al, 1988;Flores, et al, 2010;Teivens & Mörnstad, 2001). …”
Section: Introductionunclassified